2015
DOI: 10.1590/s0102-67202015000300004
|View full text |Cite
|
Sign up to set email alerts
|

Lactate as Predictor of Mortality in Polytrauma

Abstract: Background: The lactate is a product of anaerobic metabolism; it can be used as a marker on demand and availability of oxygen. Changes in lactate levels can be effectively used as a marker in resuscitation maneuvers, even in patients with stable vital signs. Aim: To verify the lactate clearance as a predictor of mortality in trauma patients, in need of intensive care. Method: A total of 851 patients were admitted in ICU, in which 146 were victims of multiple trauma; due to the exclusion criteria, were included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 14 publications
1
25
1
3
Order By: Relevance
“… Heinonen, 2014 [ 51 ] 610 Retrospective Variable Variable Failure to normalize lactate associated with increased mortality 35. Freitas, 2015 [ 52 ] 117 Retrospective 6 h 6 h No correlation between decrease in lactate and mortality 36. Dezman, 2015 [ 53 ] 3887 Retrospective ≥3 Variable Variable No decrease in lactate independent predictor of 24-h mortality Interventional 37.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… Heinonen, 2014 [ 51 ] 610 Retrospective Variable Variable Failure to normalize lactate associated with increased mortality 35. Freitas, 2015 [ 52 ] 117 Retrospective 6 h 6 h No correlation between decrease in lactate and mortality 36. Dezman, 2015 [ 53 ] 3887 Retrospective ≥3 Variable Variable No decrease in lactate independent predictor of 24-h mortality Interventional 37.…”
Section: Resultsmentioning
confidence: 99%
“…We identified twelve observational studies in trauma patients [ 42 53 ]. Three retrospective studies reported no association of change in lactate levels with mortality [ 43 , 47 , 52 ], although Manikis et al [ 43 ] reported that the duration of hyperlactatemia was associated with the development of organ failure and Billeter et al [ 47 ] noted that delayed or no reduction in blood lactate was associated with increased infectious complications. Several small studies used relatively long time intervals of 12–24 hrs [ 45 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lactate value > 4 mmol/l is rare, and is associated with systemic inflammation and needs ICU care. 25,26 In 2013, 4742 trauma patients were included in their analysis by Stephen R. Odom, who concluded that lactate values <4 mEq/l were the best death predictors in trauma patients 14 . Unlike previous research in 2015, Freitas and Franzon found that in patients treated with multiple traumas there is no association between lactate admission and mortality 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Our results are consistent with those reported by Mikkelsen et al ( 23 ). In spite of prevailing evidence that the lactate reduction influences the critically ill patient outcomes, there are five studies reporting no predictive effect of a decrease in lactate levels over time on mortality ( 24 , 25 , 26 , 27 , 28 ). Although they showed no effect on mortality, the study by Manikis et al ( 24 ) and Billeteret al ( 25 ) suggested a relationship between lactate concentration and morbidity outcomes.…”
Section: Discussionmentioning
confidence: 99%